2019
DOI: 10.1007/s00405-019-05425-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect on vestibular function of cochlear implantation by partial deafness treatment–electro acoustic stimulation (PDT–EAS)

Abstract: Purpose Although the cochlear implantation procedure does not interfere with vestibular structures directly, both the vestibulum and the cochlea share the same inner ear fluid space, and this fluid may be responsible for transferring possibly damaging forces from one to the other. The purpose of the study is to assess postoperative vestibular function after partial deafness treatment–electro-acoustic stimulation (PDT–EAS) cochlear implantation. Methods Fifty-five patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…We also confirmed that the RWA is a preferable approach for the preservation of vestibular function (7,8). We compared the frequencies of vestibular preservation between RWA and cochleostomy patients in the literature (Figure 3) (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). The median preservation rates for RWA and cochleostomy patients were 81 and 61% based on caloric testing, and 63.5 and 39% based on cVEMP, respectively.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…We also confirmed that the RWA is a preferable approach for the preservation of vestibular function (7,8). We compared the frequencies of vestibular preservation between RWA and cochleostomy patients in the literature (Figure 3) (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). The median preservation rates for RWA and cochleostomy patients were 81 and 61% based on caloric testing, and 63.5 and 39% based on cVEMP, respectively.…”
Section: Discussionmentioning
confidence: 53%
“…Chen et al reported that among the vestibular functions, the semicircular canal function was more frequently damaged ( 19 ). Sonsa et al showed that the frequencies of post-operative damage to these three vestibular functions were almost equal ( 20 ). Our present study showed that saccular function was more frequently damaged post-operatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimal preservation of residual hearing requires a more atraumatic CI surgery which can be expected to diminish injury to the vestibular organ as well. However, there are indications of some damage to the vestibular receptors of the otolith organs and semicircular canals even when using soft surgery techniques ( 42 ). Insertion speed was found to influence hearing preservation and vestibular function.…”
Section: Discussionmentioning
confidence: 99%
“…Today patients do not have to suffer from complete deafness, and also candidates with low-frequency residual hearing and unilateral hearing loss are eligible for this treatment (5). Surgery in terms of hearing preservation appears to reduce the postoperative risk of vertigo (6). While age is discussed as a potential risk factor in several studies (7,8), no significant correlation was found regarding gender and etiology of hearing loss (7,9,10).…”
Section: Introductionmentioning
confidence: 99%